2011
DOI: 10.1590/s0037-86822011005000056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and dimorphism of azole-susceptible and resistant Candida albicans isolates

Abstract: Introduction: Candida albicans is responsible for superficial or systemic infections known as candidiasis, which may be found in infected tissue as unicellular budding yeasts, hyphae, or pseudohyphae. In this study, the effects of both fluconazole and itraconazole antifungal agents on the hyphal formation and genotypic characterization of C. albicans isolates classified as either susceptible or resistant were investigated. Methods: The hyphal production of five C. albicans isolates under the action of antifung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It has been observed that there is a correlation between resistance to antifungals and the ability to undergo filamentous growth [161,169]. For azoles, when C. albicans clinical isolates with variable levels of resistance to azole antifungals were grown under filament-inducing conditions, and, in the presence of an azole drug, drug-resistant isolates were able to form hyphae more efficiently than susceptible isolates [161,170]. In C. lusitaniae , there is also an association between resistance to the polyene amphotericin B, and pseudohyphal filamentation: phenotypic switching produces a distinct phenotype (dark brown colony pigmentation on copper sulfate media), which is associated with both pseudohyphal growth as well as an slightly elevated MIC relative to the dominant “light brown” phenotype [50].…”
Section: Candida Morphogenesis Antifungal Drugs and Drug Resistancementioning
confidence: 99%
“…It has been observed that there is a correlation between resistance to antifungals and the ability to undergo filamentous growth [161,169]. For azoles, when C. albicans clinical isolates with variable levels of resistance to azole antifungals were grown under filament-inducing conditions, and, in the presence of an azole drug, drug-resistant isolates were able to form hyphae more efficiently than susceptible isolates [161,170]. In C. lusitaniae , there is also an association between resistance to the polyene amphotericin B, and pseudohyphal filamentation: phenotypic switching produces a distinct phenotype (dark brown colony pigmentation on copper sulfate media), which is associated with both pseudohyphal growth as well as an slightly elevated MIC relative to the dominant “light brown” phenotype [50].…”
Section: Candida Morphogenesis Antifungal Drugs and Drug Resistancementioning
confidence: 99%
“…are more resistant to oxidative stress 10 , and hyphal formation is higher in isolates resistant to azole drugs 11 . Taking into account these data, overcoming the oxidative phagocytic challenge seems to be critical for the establishment of candidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is the primary fungal species associated with oral candidiasis, can adhere to and colonize denture resins, and contributes to denture-related stomatitis, during which the yeast may form germ tubes and hyphae 1 . Candida albicans virulence depends on its ability to transform between the yeast and fi lamentous (pseudohyphae or true hyphae) forms 2 ; the latter is induced in human infections 3 .…”
mentioning
confidence: 99%